1969
DOI: 10.1071/ea9690497
|View full text |Cite
|
Sign up to set email alerts
|

Some nutritional aspects of feeding sorghum grain of high tannin content to growing chickens

Abstract: The grains of three sorghum varieties varying in tannin content were fed to growing chickens as 70 per cent of their diet in three experiments. Tannic acid per se was also fed as 0.1 per cent and 1.0 per cent of the grain component in one of these experiments. There was a marked growth retardation as the tannin content of the grain component rose. This retardation, whether produced by an increase in plant tannin or the addition of tannic acid per se, could only be partially alleviated by supplementation with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The depression in body weight due to OA agrees with the reports of Huff et al (1974, Prior et al (1980), and Huff and Doerr (1981) who observed that chicks fed diets containing OA had reduced performance. The depression in body weights due to TA is in agreement with the findings of Chang and Fuller (1964), Vohra et al (1966), Conner et al (1969), Rostagno et al (1973), Armstrong et al (1973Armstrong et al ( , 1974, and Dale et al (1980) who found that dietary tannic acid or diets containing high tannin grain sorghum have a detrimental effect on chick performance. At 26 days of age, body weights were significantly lower in the OA-TA combination groups than the TA group and approached being significantly lower than the OA group.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The depression in body weight due to OA agrees with the reports of Huff et al (1974, Prior et al (1980), and Huff and Doerr (1981) who observed that chicks fed diets containing OA had reduced performance. The depression in body weights due to TA is in agreement with the findings of Chang and Fuller (1964), Vohra et al (1966), Conner et al (1969), Rostagno et al (1973), Armstrong et al (1973Armstrong et al ( , 1974, and Dale et al (1980) who found that dietary tannic acid or diets containing high tannin grain sorghum have a detrimental effect on chick performance. At 26 days of age, body weights were significantly lower in the OA-TA combination groups than the TA group and approached being significantly lower than the OA group.…”
Section: Resultssupporting
confidence: 90%
“…The use of these grain sorghums with a high tannin content in poultry diets and the addition of tannic acid (TA) to experimental diets have been shown to cause reduced performance in chickens (Chang and Fuller, 1964;Vohra et al, 1966;Conner et al, 1969;Rostagno et al, 1973;Armstrong et al, 1973Armstrong et al, , 1974. Chang and Fuller (1964) found that feeding high tannin grain sorghums resulted in growth retardation that was similar in magnitude to that caused by equivalent levels of tannic acid per se.…”
Section: Introductionmentioning
confidence: 93%
“…The RSM used in this experiment contained 06% water-extractable tannin and tannin has been associated with depressed gain and poorer food conversion (Rostagno et al, 1973) although this is not a consistent feature (Connor «/ al., 1969). • -• • Apart from toxins, RSMs may differ in their contents of available amino acids.…”
Section: -7 5-8mentioning
confidence: 98%
“…can cause liver and kidney disorders in rabbits and rats (Arheleger et al 1965, Boler et al 1966, Ca.mp et al 1967). Dietary tannin also has been shown to reduce growth rates in chickens (Vohra et al 1965, Fuller et al 1967, Conner et al 1969, Armstrong et al 1974, Kubena et al 1983). Quercetin (a flavonoid) and tannic acid (a hydrolyzable tannin).…”
Section: Low Population Densities Of Ruffed Grouse In Thementioning
confidence: 99%